Real Time Monitoring System Dari Active Solar Photovoltaic Tracker Berbasis Internet Of Things - Izra Bagus Kurniansyah; Ferdian Ronilaya; Muhammad Fahmi Hakim (Politeknik Negeri Malang, 2020)
There are still monitoring system in Solar Power Plant that do it manually. From here the idea emerged to develop a monitoring system using the IoT concept so that monitoring on Solar Power Plant that can be monitored just by looking at the website page, so current and voltage data can be easily monitored. This monitoring system is used to monitor the current and voltage of a solar power plant with solar cell capacities of 50WP, 80WP, and 100WP. In the application of using Solar Power Plant that, there is a current and voltage starting from the solar cell output, accumulator output, AC load input, and DC load input. The monitoring results that have been carried out will then be automatically sent to the Thingspeak application using the SIM800L Module. The thingspeak application will send data in the form of numbers and graphics in real time. By comparing the value of the measurement results on the Arduino and the Thingspeak application, the value of the percentage of reading errors on the measuring instrument is obtained. 3. In accordance with the tests that have been carried out, the percentage of read errors / errors can occur because of the reading accuracy of the current sensor measurements and AC-DC voltage sensors with different thingspeak applications. Each sensor has a percentage value of 0.16% AC & DC voltage sensor measurement error, 1.2% AC & DC current sensor, and 2.8% data transmission observation.